Dynamics of dairy production in Uttaranchal hills - SINGH, VIR; TULACHAN, PRADEEP M; PARTAP, TEJ (The Indian Journal of Animal Sciences, 2014)
An analysis of temporal changes in ruminant population in Uttaranchal Hills between 1961 and 1999 shows an overall increase of about 15% in total ruminant population. The most noticeable change over a period of about 4 decades is an overwhelming increase in the population of buffaloes (55%) and of goats (50%). A considerable decline in the population of cattle (5%) and sheep (14%) are another noteworthy changes. With gradual emphasis on dairy sector, milk production in Uttaranchal hills has increased from mere 419 thousand MT in 1979-80 to about 715 thousand MT in 1999-2000, recording an impressive rise of 71 % over this period. Whereas milk production from cows has increased only 19%, buffalo milk production has leapt by 111 % over this period. The milk production increase in Uttaranchal hills, thus, is largely thanks to buffaloes’ contribution. Presently buffalo population contributes more than 60% to the total milk production in the region. Milk productivity per animal has increased over a period of 2 decades. In case of a cow it has increased from an average of 1.33 kg/day in 1979-80 to 2.30 kg/day in 1999-2000. An average increase in milk yield from 2.55 kg/day to 3.71 kg/day over the same period has been recorded for a buffalo. Lactation yield increase per cow (73%) has been far higher than per buffalo (45%). This is attributable to the institutional policies and programmes focussing on cows and negligence of buffaloes.